Allometry of evaporative water loss in marsupials: Implications of the effect of ambient relative humidity on the physiology of brushtail possums (Trichosurus vulpecula) - Cooper, Christine; Withers, P. (Oxford University Press, 2008)
To better understand the effects of ambient relative humidity (RH) on physiological variables and the implications of RH-correcting evaporative water loss (EWL) data for marsupials, we examined the effect of RH on EWL, body temperature (Tb), metabolic rate (MR) and thermal conductance (C) of the brushtail possum (Trichosurus vulpecula), a medium-sized marsupial. Correcting EWL data for 27 species of marsupial for water vapour pressure deficit (WVP) in the chamber during measurement significantly increased, rather than decreased, the variability of the allometric relationship for EWL. For the brushtail possum, both Ta and RH significantly affected EWL. At Ta = 25C, EWL was independent of RH at 63 % RH, but decreased linearly at higher RHs. At Ta = 30C, EWL was significantly related to RH from 26-92 % RH. There was a significant effect of Ta on Tb and Cdry (higher at 30C) but no effect of RH. For MR and Cwet, there was a significant effect of Ta (MR higher and Cwet lower at 25C), and RH at Ta = 30C (MR higher and Cwet lower at the lowest RH) but not at 25C. Our results indicate that brushtail possums do not necessarily show the linear relationship between ambient RH and EWL expected for an endotherm, possibly because of behavioural modification of their immediate microclimate. This may account for the failure of WVP deficit correction to improve the allometric EWL relationship for marsupials. Chamber RH is also an important environmental factor to be considered when measuring standard physiological variables such as MR and Cwet.